Responses of Leaf Anatomy and CO2 Concentrating Mechanisms of the Aquatic Plant Ottelia cordata to Variable CO2 - Huang, Wenmin; Han, Shijuan; Xing, Zhenfei; Li, Wei (Frontiers in Plant Science, 2020)
Acclimation to variable CO2 was studied in floating leaves of the freshwater monocot Ottelia cordata grown in either low or high CO2. The most striking anatomical variations responding to high CO2 included the enlarged upper epidermal cells and the decreased area of epidermal chloroplasts. Stomata that distributed on the upper surface, and the stomatic chamber area, showed no significant response to high CO2. pH-drift experiments indicated that floating leaves of O. cordata were able to use bicarbonate regardless of CO2 concentrations. Photosynthetic enzyme activities and patterns of organic acids fluctuation confirmed that floating leaves of O. cordata can operate CAM only at low CO2, and perform C4-like metabolism at both high and low CO2. Overall, the present results imply that the floating leaves of O. cordata does not just rely on the atmospheric CO2 for its inorganic carbon, but is also dependent on CO2 and bicarbonate in the water. By showing these effects of CO2 variation, we highlight the need for further experimental studies on the regulatory mechanisms in O. cordata floating leaves, that prevent futile cycling among the three CO2 concentrating mechanisms (bicarbonate use, C4 and CAM metabolism) and the strategy for exploiting atmospheric CO2, as well as studies on the detailed biochemical pathway for C4 and CAM metabolism in this species.